Reform of state-owned enterprises in Viet Nam to increase performance and profit - Kunmin Kim; Nguyen Anh Tru (Asian Development Bank Institute (ADBI), 2019)
In Viet Nam, the reform of state-owned enterprises (SOEs) in recent years has become an essential mission to improve their performance in the context of international economic integration. It also represents the commitment of the Vietnamese Government to renovating economic institutions as well as constructing a market-oriented economy. This article aims to examine the reform of SOEs in Viet Nam. It finds that the net revenue positively affects the profit before taxes of SOEs, while sales expenses exert a negative impact on the profit before taxes. The article recommends policies to the government and SOEs to enhance performance and foster the achievement of the reform, including the enhancement of the roles of the state in SOEs, the transparency procedure of the reform, the improvement of the government's control and inspection in the equitization and divestment of SOEs, the selection of appropriate methods for equitization and divestment, the exact assessment of SOEs' value, and the consideration of the particular characteristics of different sectors.
Keywords: G32; P31; 330; Reform; state-owned enterprise; Viet Nam; performance; profit